Membangun Mental Entrepreneur Santri melalui Perspektif Maqashid Syariah - Sunaji Sunaji (LPPM Ma'had Aly Sunan Drajat Lamongan, 2025)
This study explores the role of Maqashid Syariah in shaping the entrepreneurial mindset of santri (Islamic boarding school students). In the modern era, fostering entrepreneurship among santri is crucial for developing independence, creativity, and ethical business practices. Maqashid Syariah, which emphasizes the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal), provides a moral and ethical framework for building character-based entrepreneurship. This research uses a qualitative descriptive-analytical approach with a case study method, involving observations, interviews, and documentation at selected pesantren with active entrepreneurship programs. The results reveal that integrating Maqashid Syariah principles into santri activities enhances their ethical awareness, creativity, and resilience in entrepreneurial ventures. Santri learn to manage resources responsibly, innovate products ethically, and balance profit-making with social responsibility. The study concludes that Maqashid Syariah not only supports spiritual development but also strengthens entrepreneurial character, preparing santri to become ethical, competent, and socially responsible entrepreneurs. This research provides insights for pesantren educators to develop curriculum and programs that effectively combine Islamic principles with entrepreneurial training